Industrial IT revolution through wireless sensor network technologies - Petersen, S.; Carlsen, S.; Talevski, Alex (Institute of Electrical and Electronics Engineers (IEEE)., 2008)
Recent advances in wireless technology have enabled the deployment of low-cost wireless solutions that are capable of robust and reliable communication in the resources and manufacturing industries. Wireless application areas such as networking, sensors, and asset tracking offer great opportunitiesfor production optimization where the use of wired counterparts prove to be prohibitive, expensive or difficult to implement and maintain. Data that is gathered from such wireless devices and networks is quite valuable and leads to new and innovative solutions that may aid the resources and manufacturingindustries in preventing problems, reducing operating costs and generally improving operations. Using wireless sensor networks, we propose new intelligent solutions that aid factory monitoring, maintenance, error tolerance and security and safety. In this paper, related wireless technologies are discussed.